What is \( (f \cdot g)(x) \) ? \[ \begin{array}{l}f(x)=x+2 \\ g(x)=-4 x+3 \\ \text { Write your answer as a polynomial or a rational function in simplest form. }\end{array} . \begin{array}{l}\text { ? }\end{array} \text { ? } \]
Real Tutor Solution
Answer
Solution
Reviewed and approved by the UpStudy tutoring team
Extra Insights
To find \( (f \cdot g)(x) \), we need to multiply the two functions \( f(x) \) and \( g(x) \). First, substitute the given functions: \[ f(x) = x + 2 \] \[ g(x) = -4x + 3 \] Now, multiply them together: \[ (f \cdot g)(x) = f(x) \cdot g(x) = (x + 2)(-4x + 3) \] Expanding this product using the distributive property (also known as the FOIL method for binomials): 1. First: \( x \cdot (-4x) = -4x^2 \) 2. Outside: \( x \cdot 3 = 3x \) 3. Inside: \( 2 \cdot (-4x) = -8x \) 4. Last: \( 2 \cdot 3 = 6 \) Combining these results: \[ -4x^2 + 3x - 8x + 6 = -4x^2 - 5x + 6 \] Therefore, the answer in simplest form is: \[ (f \cdot g)(x) = -4x^2 - 5x + 6 \]